2015 IEEE International Symposium on Circuits and Systems (ISCAS) 2015
DOI: 10.1109/iscas.2015.7168825
|View full text |Cite
|
Sign up to set email alerts
|

Pespectives of TFET devices in ultra-low power charge pumps for thermo-electric energy sources

Abstract: The superior electrical characteristics of the heterojunction III-V Tunnel FET (TFET) devices can outperform current\ud technologies in the process of energy harvesting conversion at ultra-low power supply voltage operation (sub-0.25 V). In this work, it is\ud shown by simulations that a cross-coupled switched-capacitor topology with GaSb-InAs TFET devices present better conversion\ud performance compared to the use of Si FinFET technology at low temperature variations\ud (¿T < 3 ºC) when considering a thermo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…10 (a) a ring oscillator powered by the output of the rectifier is required for generating two non-overlapped clock signals that are applied to a multi-stage gate crosscoupled charge pump (GCCCP). In [16] it was shown by simulations that a TFET-based GCCCP can double its input voltage with magnitudes as low as 80 mV. In this work, the charge pump is required to charge the capacitor connected to the node Vddstartup.…”
Section: A Startup Circuitmentioning
confidence: 99%
See 1 more Smart Citation
“…10 (a) a ring oscillator powered by the output of the rectifier is required for generating two non-overlapped clock signals that are applied to a multi-stage gate crosscoupled charge pump (GCCCP). In [16] it was shown by simulations that a TFET-based GCCCP can double its input voltage with magnitudes as low as 80 mV. In this work, the charge pump is required to charge the capacitor connected to the node Vddstartup.…”
Section: A Startup Circuitmentioning
confidence: 99%
“…Due to the bandto-band tunneling (BTBT) carrier injection mechanism, the TFET device presents a sub-threshold swing (SS) below 60 mV/dec (room temperature) and low leakage current [12][13][14]. These characteristics make this technology attractive for ultra-low voltage/power front-end rectifiers and switched capacitors, as shown by recent works [15][16][17]. The decrease of energy per switch also allows the design of more efficient digital cells when compared to conventional CMOS [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Benchmarking based on Si- and III–V-based state-of-the-art TFET devices with data published by various research groups. We have chosen to use data for SS vs I DS per unit width for both n-TFET (denoted by circle with solid line) and p-TFET (denoted by diamond with solid line) devices which have shown SS near or less than thermal limit (60 mV/dec) at room temperature. ,,, …”
Section: Transition From Mosfets To Energy-efficient Tfet Devicesmentioning
confidence: 99%
“…As an example, the work reported in [9] show improvements in the performance of TFET-based charge-pump converters compared to the application of the FinFET technology at sub-400 mV levels. In [10] we have shown that a gate crosscoupled charge-pump topology with TFETs powered by a thermogenerator presents a peak power conversion efficiency (PCE) of 74% for a temperature variation of 1 K (Vin=80 mV). In another work, the authors have shown similar PCE improvements in RF passive rectifiers based on TFETs for input power levels below -30 dBm (typical far-field ambient RF-power) [11].…”
Section: Introductionmentioning
confidence: 99%